Gender differences in the mental health impact of the COVID-19 lockdown: Longitudinal evidence from the Netherlands. (September 2021) - Vloo, A.; Alessie, R.J.M.; Mierau, J.O.; ,; Boezen, Marike H.; Mierau, Jochen O.; Franke, Lude; Dekens, Jackie; Deelen, Patrick; Lanting, Pauline; Vonk, Judith M.; Nolte, Ilja; et al.
Abstract: Recent contributions highlighted gender differences in the mental health consequences of COVID-19 lockdowns. However, their cross-sectional designs cannot differentiate between pre-existing gender differences and differences induced by lockdowns. Estimating fixed-effects models using longitudinal data from the Lifelines biobank and cohort study with repeated mental health measurements throughout the lockdown, we overcome this caveat. Significant gender differences in mental health during the lockdown were found, where women experienced more depression symptoms and disorders and men experienced more anxiety symptoms and disorders stemming from the lockdown. Policymakers need to keep in mind that the COVID-19 lockdowns have different effects on mental health for men and women. Highlights: Mental health consequences of the COVID-19 pandemic appear to show strong gender differences. Current studies using cross-sectional data cannot differentiate between pre-existing and pandemic induced gender differences. Using longitudinal data we show that the pandemic had different mental health impacts on men and women. Women experienced more depression, while men experienced more anxiety.